Proceedings of the 18th International Conference on INFORMATICS in ECONOMY Education, Research and Business Technologies 2019
DOI: 10.12948/ie2019.04.17
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Ict Carbon Footprints Through Adoption of Green Computing

Abstract: A significant economic, environmental and sustainability topic in information and communication technology (ICT) and e-business sectors is green computing. An aspect of green informatics, green computing is gaining attention because of its wide-ranging benefits over traditional computing; factors that inhibit the adoption of green computing are therefore of vital concern. This paper investigates the benefits of green computing including economic, social and environmental impacts, especially those of e-waste. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…33 46 With the deterioration of memory capabilities among vulnerable populations, reminder programs can help them cope with their daily lives and adapt to their physiological changes. 58 59 Thus, adherence technologies should consider incorporating reminders to assist patients with their medical and treatment goal achievement . In addition, the findings of this review showed that user-friendly interfaces that facilitate communication and the versatility aspects of the technologies can help in its success in supporting adherence, which should be considered by technology designers and developers .…”
Section: Discussionmentioning
confidence: 99%
“…33 46 With the deterioration of memory capabilities among vulnerable populations, reminder programs can help them cope with their daily lives and adapt to their physiological changes. 58 59 Thus, adherence technologies should consider incorporating reminders to assist patients with their medical and treatment goal achievement . In addition, the findings of this review showed that user-friendly interfaces that facilitate communication and the versatility aspects of the technologies can help in its success in supporting adherence, which should be considered by technology designers and developers .…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide concern over climate change has increased, and nations are holding summits to address and stop global warming. Information technologies have been helpful in achieving the goals of environmental preservation, and one strategy is the use of green computing [20]. The main goals of GIT are to use less hazardous materials, utilize less energy, maximize profits, and raise awareness of the benefits of computer waste that may be recycled or biodegraded [21].…”
Section: Green Information Technology Applications In Business Proces...mentioning
confidence: 99%
“…Data mining, generic algorithms, and neural networks are gradually applied in sustainable consumption research, that enables more accurate and better visualized results (Wang et al, 2019). Managing efficient energy use is a commonly discussed issue that takes into consideration the climate change impact analysis with regard to the energy use of campus buildings (Fathi and Srinivasan, 2019), life-cycle assessment of energyconsuming products (Ross and Cheah, 2019) as well as the adaptation of green computing to reduce the carbon footprint of ICT (Airehrour et al, 2019). The "blue" cluster seems to reveal methodologies considered in climatology, urbanization, and adaptive management.…”
Section: Biodiversitymentioning
confidence: 99%